FUNGSI AGAMA BAGI MASYARAKAT DALAM PERSPEKTIF SOSIOLOGI AGAMA (STUDI KASUS DALAM KEHIDUPAN MASYARAKAT HINDU DI BALI) - I Dewa Gede Darma Permana dewa_permana21 (UHN IGB Sugriwa Denpasar, 2022)
The function of religion is something that deserves to be discussed. This is because, the function of religion, which should be useful for creating a harmonious life, is currently being used by some individuals to hurt and even kill. In view of this, researchers are interested in examining more deeply the function of religion for people's lives, especially in the life of the Hindu community in Bali. In this research, several problem formulations were formulated, among others; the essence of religion, the function of religion in people's lives, as well as the variations in the functions of that religion with the life of the Hindu community in Bali. Using this type of qualitative research, with the method of collecting data from literature studies, the results of this study indicate that the Hindu community in Bali has so far been able to implement the function of religion as it should be as evidenced by various teachings and ceremonies such as; equal braya, tirta, ngulapin and others.